2021
DOI: 10.1080/08830185.2021.1955876
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid in macrophage polarization: The significant role in inflammation and cancer

Abstract: Metabolite lactic acid has always been regarded as a metabolic by-product rather than a bioactive molecule. Recently, this view has changed since it was discovered that lactic acid can be used as a signal molecule and has novel signal transduction functions both intracellular and extracellular, which can regulate key functions in the immune system. in recent years, more and more evidence has shown that lactic acid is closely related to the metabolism and polarization of macrophages. During inflammation, lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 130 publications
3
57
0
Order By: Relevance
“…Lactic acid is a regulator of macrophage metabolism and can prevent excessive inflammation. Studies have revealed a new connection between lactic acid and the control of uterine inflammation, and found that high levels of lactic acid act on uterine GPR81 and downregulate pro-inflammatory genes (Zhou et al, 2021). Taurine is an endogenous anti-injury substance in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid is a regulator of macrophage metabolism and can prevent excessive inflammation. Studies have revealed a new connection between lactic acid and the control of uterine inflammation, and found that high levels of lactic acid act on uterine GPR81 and downregulate pro-inflammatory genes (Zhou et al, 2021). Taurine is an endogenous anti-injury substance in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, secretion of TNF-a by macrophages is inhibited by acidic pH (112). Additionally, long term effect of exogenous lactate in M1 macrophages, trigger an endogenous 'lactate clock' that induce an M2 phenotype by metabolic reprograming through the epigenetic mechanism by lactylation and acetylation of histone H3 (113,114). This effect could to assist with repairing collateral damage produced by the host during infection and to explain the anti-inflammatory effects of lactate after 24 h (85,115,116).…”
Section: Lactate Activity In Macrophages and Mast Cellsmentioning
confidence: 99%
“…Studies show lactate enhances the production of MDSC from the bone marrow of mice while suppressing NK cells leading to weakened cytotoxicity [ 201 ] ( Figure 1 C). Furthermore, lactate skews macrophages toward the tumor-promoting M2 phenotype and upregulates PD-L1 to enhance immune escape [ 202 , 203 , 204 ]. Therefore, an increased lactate concentration in the TME serves as not only a potential therapeutic target, but also a poor prognosticator [ 198 ].…”
Section: Tumor Stroma Mediators Chemical Components and Physical Factors Constitute The Tumor Microenvironment (Tme)mentioning
confidence: 99%